2016
DOI: 10.1208/s12249-015-0440-8
|View full text |Cite
|
Sign up to set email alerts
|

Development, Optimization, and Evaluation of Carvedilol-Loaded Solid Lipid Nanoparticles for Intranasal Drug Delivery

Abstract: Abstract. Carvedilol, a beta-adrenergic blocker, suffers from poor systemic availability (25%) due to firstpass metabolism. The aim of this work was to improve carvedilol bioavailability through developing carvedilol-loaded solid lipid nanoparticles (SLNs) for nasal administration. SLNs were prepared by emulsion/solvent evaporation method. A 2 3 factorial design was employed with lipid type (Compritol or Precirol), surfactant (1 or 2% w/v poloxamer 188), and co-surfactant (0.25 or 0.5% w/v lecithin) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…The stability studies revealed the physical stability of SLN after 3 months storage and there was no significant change observed in the data. Zeta potential is a key Factor used for the evaluation of the stability of colloidal dispersions [5,20]. As observed from the results F3 formulation was negatively charged, indicating a relatively good stability and quality.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The stability studies revealed the physical stability of SLN after 3 months storage and there was no significant change observed in the data. Zeta potential is a key Factor used for the evaluation of the stability of colloidal dispersions [5,20]. As observed from the results F3 formulation was negatively charged, indicating a relatively good stability and quality.…”
Section: Discussionmentioning
confidence: 76%
“…Although CL is well absorbed in the gastrointestinal tract, it is extensively metabolized in the liver leading to decreased bioavailability of about 25 % [5]. The oral bioavailability remains low because of significant first-pass hepatic metabolism by cytochrome P450 and also because of its short plasma halflife [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was prepared by placing a drop of PHCL loaded ethosomes that was previously diluted 50 fold with double-distilled water onto a 400-mesh copper grid coated with carbon film and followed by negative staining with 1% phosphotungstic acid. The sample was dried in the air before TEM observation [25].…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Compatibility of β-blockers with lipid excipients has been established (7) and some β-blockers such as propranolol (8), atenolol, metoprolol (8)(9), pindolol, labetolol (7) and carvedilol (9) have been encapsulated in solid lipid based polymers for oral (8,10), topical (11), intranasal (12) and ophthalmic (13) routes of administration. β-blockers have also been formulated in the form of mucoadhesive tablets containing propranolol loaded chitosan-gelatin microparticles (14)(15).…”
mentioning
confidence: 99%